P.S. be eleven - Williams-Garcia, Rita (Amistad, 2015)
Amidst the changes overtaking her world in the 1960s, from the rise of the Jackson 5 to her father's new girlfriend, eleven-year-old Delphine struggles to keep her life in order. As she contends with one issue after another, writing letters to her mother to gain confidence, she gains the strength to push forward while trying to stay true to her mother's insistence that she not grow up too fast.